PENAMBATAN MOLEKUL DAN PREDIKSI UJI TOKSISITAS PADA SENYAWA TURUNAN INHIBITOR GATA-2 SEBAGAI PENINGKAT TRANSKRIPSI ERITROPOIESIS - Dona Suzana; Ashfar Kurnia, Dina Melia Oktavilantika, Lathvi Masyithah (CV. ADIBA AISHA AMIRA, 2022)
Anemia is a condition in which the number of red blood cells or the amount of hemoglobin, a protein responsible for transporting oxygen throughout the body, is below normal. The condition of chronic kidney disease causes a decrease in hemoglobin levels in the body so that it affects the proliferation of red blood cells. The search for compounds to stimulate the process of red blood cell proliferation without involving erythropoietin was carried out. Pyrrotiogatain compounds are believed to increase the proliferation of red blood cells, but are reported to have serious toxicity. Then modification of the molecule is carried out to find the effectiveness which has lower toxicity. Several pyritiogartain derivatives have been produced which are effective with molecular tethering and determination of the productive toxicity